Fixed Asset Accounting at PT Perkebunan Nusantara II Tanjung Morawa - Muhammad Syafii Pranoto (Rowter Journal, 2022)
The purpose of this study is to determine whether the fixed asset accounting at PT Perkebunan Nusantara II Tanjung Morawa has keen in accordance with Statement of Financial Accounting Standard No.16 of 2012. In this study, the type of data used are secondary data, that are all informations concerning with fixed assets. Data are collected by doing interview and documentation techniques. Data analyzed by using descriptive method. The findings show that fixed asset accounting at PT Perkebunan Nusantara II Tanjung Morawa has keen in accordance with Statement of Financial Accounting Standard No.16 of 2012.